Combined ultrasound and IVU for the management of childhood urolithiasis: a case report - Ahmad Saad, Fathinul Fikri (Universiti Putra Malaysia Press, 2012)
The incidence of ureteric calculus as a cause for severe abdominal pain in children is mounting, especially in the tropical country. The course of illness may be non-specific but a swift detection via non-invasive imaging modalities singly or in combination may avert unnecessary radiation hazard and futile surgery in a young child. In this paper, we discussed a case of an 11 year-old boy who was presented with a sudden onset of the right side severe abdominal colic whose a bedside ultrasound was positive for hydronephrosis for which localisation of stone was further confirmed via a low dose limited intravenous urography (IVU). It is important to note that data available on the value of a combined ultrasound and the limited IVU in an emergency setting when urolithiais is being suspected in children with abdominal pain are particularly scarce. Hence, this case documented the potential value of a combined ultrasound and a limited IVU study as a unique combined armamentarium used in a suspected childhood urolithiasis in the tropics.